2011
DOI: 10.1093/molehr/gar074
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression is altered after bisphenol A exposure in human fetal oocytes in vitro

Abstract: Bisphenol A (BPA) is a 'weak' endocrine disruptor. The effect of BPA on human reproduction is controversial but has been related to meiotic anomalies, recurrent spontaneous abortion, abnormal karyotypes, the diminishing of oocyte survival, delay in meiotic progression and an elevated rate of MLH1 foci in vitro. The aim of this study is to characterize the gene expression of human fetal oocytes in culture as well as to evaluate the effect of BPA in cultured human oocytes. To accomplish our objective, 12 ovaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 64 publications
0
34
0
3
Order By: Relevance
“…Additionally, previous studies have also demonstrated that BPA exposure impairs the double-strand break repair machinery, increases the number of homologous recombination protein RAD-51 foci in late pachytene, 14 elevates mismatch repair-related MLH1 foci, 9, 15 and upregulates the expression of genes involved in DSB generation (Spo11), signaling (H2AX), and repair (RPA, BML). 36 These results suggest that exposure to a low dose of BPA may lead to the persistence of mDSBs by inhibiting their repair, although high doses of BPA have been reported to be genotoxic. 37 Subsequently, these unresolved mDSBs in pachytene spermatocytes result in the disruption of meiotic progression and chromosome abnormalities, such as asynapsis, chromosomal aberrations, and interrupted regions of SYCP3 staining, as also demonstrated by previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, previous studies have also demonstrated that BPA exposure impairs the double-strand break repair machinery, increases the number of homologous recombination protein RAD-51 foci in late pachytene, 14 elevates mismatch repair-related MLH1 foci, 9, 15 and upregulates the expression of genes involved in DSB generation (Spo11), signaling (H2AX), and repair (RPA, BML). 36 These results suggest that exposure to a low dose of BPA may lead to the persistence of mDSBs by inhibiting their repair, although high doses of BPA have been reported to be genotoxic. 37 Subsequently, these unresolved mDSBs in pachytene spermatocytes result in the disruption of meiotic progression and chromosome abnormalities, such as asynapsis, chromosomal aberrations, and interrupted regions of SYCP3 staining, as also demonstrated by previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Brieño-Enriquez et al (2011, 2012) reported that BPA (1–30 μM) increased oocyte degeneration by impairing meiotic progression in cultured human fetal oocytes and that, similar to mouse studies, human fetal oocytes that progressed to prophase exhibited increased levels of recombination (MLH1 foci) and gene expression changes. BPA also increased methylation errors in differentially methylated regions of maternally imprinted genes of oocytes in cultured preantral follicles of C57/BL6xCBA/Ca mice (Trapphoff et al 2013).…”
Section: Early Oogenesis and Ovarian Follicle Formationmentioning
confidence: 77%
“…In connected studies it has been demonstrated that the exposure of human oocytes to BPA is linked to up-regulation of genes involved in meiotic processes connected to double strand breaks repair progression (Brieno-Enriquez et al 2012). A non-linear response to BPA doses on the incidence of MII oocytes with aligned chromosomes has also been determined (Machtinger et al 2013).…”
Section: Influences Of Bpa On Reproduction Of Femalesmentioning
confidence: 99%